The Influence of Public Perception in Forming Satisfaction and Continuance Intention of Using the New PLN Mobile Application in Surabaya - Teguh Priya Utama; Sri Setyo Iriani; Sanaji Sanaji (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study analyzes the influence of public perception on satisfaction and continuance intention in using the New PLN Mobile application in Surabaya. The background of this research is the increasing adoption of digital public service applications, while user retention remains a critical issue. The objective of this study is to examine how perceived usefulness and perceived ease of use affect user satisfaction and continuance intention. This research applies a quantitative approach using the Technology Acceptance Model (TAM) and Expectation Confirmation Model (ECM). Data were collected through questionnaires distributed to active PLN Mobile users in Surabaya. The data were analyzed using multiple linear regression to test the relationships among variables. The results show that perceived usefulness and perceived ease of use significantly influence user satisfaction. Furthermore, user satisfaction has a significant effect on continuance intention. These findings indicate that user perception plays a key role in determining long-term adoption of digital public service applications. This study provides implications for improving user-centered design in government digital services.